The Impact of the Smart Village Program on Community Empowerment in Rural Areas in South Lampung Regency, Lampung Province - Widya Kesuma; Hyronimus Rowa; Tjahyo Suprayogo (INFOKUM, 2025)
Village development in South Lampung Regency is still not optimal in empowering its people. As an effort to overcome this problem, the South Lampung Regency Government implemented public policy in the field of technology-based village development with the Smart Village Program. The purpose of the study was to analyze the influence of the Smart Village program on village community empowerment and to identify strategic solutions for the development of the Smart Village program. This study used a mixed method explanatory sequential design approach and SWOT analysis. The results of the study showed that the Smart Village Program had a significant influence on village community empowerment in South Lampung Regency with a significance value of the f test of 0.000, a t test of 0.000, and a coefficient of determination of 0.592 indicating that 59.2% of the variation in village community empowerment can be explained by the Smart Village Program. This is reinforced by the findings of the qualitative approach that the Smart Village Program has a significant contribution in empowering village communities, especially in providing access to information, encouraging active participation, and protecting local values ​​and resources. However, the success of program implementation still varies between villages, depending on the readiness of human resources, coaching facilities, and institutional strengths in each region. The resulting strategic solution recommendations include optimizing digital services, strengthening village capacity and mentoring, reducing inequality through independent initiatives, and ongoing monitoring and evaluation.